The Impact of Computer Assisted Translation (CAT) Tools on Translator Training - Faiza BOUKHELEF (Altralang Journal, 2024)
In recent years, the field of translation has been greatly influenced by advances in computer-assisted translation tools. These tools have not only revolutionized the translation process but also significantly impacted translator training. The integration of technology into the translator's toolkit has reshaped the way translators work and the skills they should succeed in the modern translation industry. This article investigates the increasing influence of computer-assisted translation tools on translator training and its implications for the future of the profession. The aim of this paper is to explore to what extent the development of CAT (computer-assisted translation) tools affects the environment of professional translators and the areas of teaching and learning. This research delves into the growing impact of CAT tools on translator training, including the evolving skills required by professional translators and the changing landscape of the translation industry. In addition, this paper investigates the implications of CAT tools on teaching and learning in the field of translation, focusing on how these tools shape the curriculum and pedagogy of translation programs. This exploration will provide valuable insights into the intersection of technology and translation, offering a comprehensive understanding of the effects of CAT tools on professional translators and the education and training of future translators.